2019
DOI: 10.3390/ma12162553
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Localized Vibration during Welding on the Microstructure and Mechanical Behavior of Steel Welds

Abstract: The use of vibratory welding is treated with some caution in the industry due to inconsistent beneficiary results. Here, a partial explanation is suggested by the differentiation between global vibrational effects (GVEs) and local vibrational effects (LVEs), and the latter is investigated experimentally. Two structural plates of steel are welded at three frequency/amplitude combinations using manual gas metal arc welding in an experimental setup that ensures only LVEs. After welding, tensile tests, microhardne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…However, these properties depend to some extent on the material selected, process settings, and part shape [ 37 ]. The use of digital image correlation (DIC) with tension tests [ 36 , 64 , 65 ] is recommended for measurement of the static mechanical properties, while dynamic pulse-echo ultrasonic non-destructive test (NDT) with a time-of-flight (TOF) sound velocity analysis is recommended for measurement of the elastic constants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these properties depend to some extent on the material selected, process settings, and part shape [ 37 ]. The use of digital image correlation (DIC) with tension tests [ 36 , 64 , 65 ] is recommended for measurement of the static mechanical properties, while dynamic pulse-echo ultrasonic non-destructive test (NDT) with a time-of-flight (TOF) sound velocity analysis is recommended for measurement of the elastic constants [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 c) exhibits characteristic peaks at 3367 cm −1 , 2879 cm −1 , and 1570 cm −1 corresponding to O–H stretching, C–H symmetric and asymmetric stretching, and NH bending of the primary amine, respectively 42 . Notably, bands at 1645 (CO stretching of amide I) and 1550 (NH bending of amid II) are not visible, probably due to overlapping with others 44 . The CH 2 bending and CH 3 symmetrical deformations (C–O stretching vibration of CH 2 OH groups) are detected at around 1462 cm −1 and 1377 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Two different vibration setups i.e., local vibration effect (LVE) and global vibration effect (GVE), and the effect of these vibration setups on the mechanical properties and microstructural behaviour was investigated. Authors found that GVE has a significant effect on the microstructure and mechanical properties compared to LVE [12].…”
Section: Literature Review 21the Effect Of Vibratory Assisted Welding (Vaw)mentioning
confidence: 99%